Blog corporativo para atrair o público: o caso da tecnisa - Wolff, Fernanda (2012)
This study reflects on the traditional organizational communication and its impact in the digital environment, focusing on corporate blogs. The blog Tecnisa - a Brazilian construction company based in Sao Paulo, but with over 20 branches throughout Brazil - was selected as a case study because it is a pioneer in the real estate sector. The main objective was to understand how the company establishes communication with its public through the blog. To this end, we have analyzed the five most commented posts of different sections of the blog Tecnisa. A total of 3490 comments were analyzed based on the theoretical framework used in this study for organizational communication and corporate blogs. Among the authors stand out Marchiori (2006), Kunsch (2006), Grando (2006), Hewitt (2007) and José Orihuela (2007). A research review on Tecnisa, as well as an interview with the social media digital consultant complement the methodological procedures used in this case study. Digital communication is essential within the dynamic environment of modern organizations, but the interaction occurs only when there is active participation of the public and employees of a company.